Customer advocacy and brand development - Lawer, Christopher; Knox, Simon (Emerald Group Publishing Limited, 2006)
Purpose – The purpose of this article is to define and explore the strategic value of customer advocacy through the lens of the brand management literature.  Design/methodology/approach – The paper reviews recent analysis of the value and vulnerabilities of brands and branding in order to understand why customer advocacy is becoming an attractive strategic option for many firms. A model of empowered consumer value drivers is constructed to demonstrate how they are becoming an important source of brand value. A framework for brand management in a customer advocacy context is introduced and examples of companies pursuing advocacy-based strategies and practices are illustrated.  Findings – Through careful brand management, customer advocacy is capable of unlocking new consumer value.  Originality/value – The paper offers a discussion of the opportunities presented to brand management when developing customer advocacy.
Keywords: customer loyalty; brand management; consumer behaviour